THE BEST INTEREST OF THE CHILD PRINCIPLE: A COMPARATIVE STUDY OF LEGISLATIVE AND JUDICIAL RECOGNITION IN CHILD PROTECTION AND FAMILY LAWS IN AUSTRALIA AND MALAYSIA - ARUMUGAM, MARINI; KARIM, MOHAMMAD ERSHADUL (Journal of Malaysian and Comparative Law, 2025)
The best interest of the child principle has played a significant role in achieving children’s rights around the world since the adoption of the United Nations Convention on the Rights of the Child, 1989 (“CRC”). For example, Australia has a clear legislative as well as judicial assertion of the best interest of the child principle. However, there are no general provisions that incorporate the best interest of the child principle within Malaysia’s main child protection laws, despite the country being a treaty state of the CRC. Research has been conducted to explore the incorporation of the best interest of the child principle within the Sharia perspective in the Malaysian context; however, there is limited research on the incorporation and adoption of the principle within the general children and non-Muslim family law legislations in Malaysia. The lack of universal incorporation of the principle within federal legislation in Malaysia and the absence of supporting legislative guidelines to determine the principle has been a source of limitation for the state and other actors. Employing doctrinal legal research methods and comparative law methodology, this research examines and analyses the legal framework concerning the incorporation and application of the best interest of the child principle, both in Malaysia and Australia. The findings of this research indicate that in comparison to Australia, Malaysia lacks specific provisions for the best interest of the child principle, pursuant to Article 3 of the CRC. Furthermore, there is no clear and comprehensive legitimate guidelines on the application of the principle in key child protection and non-Muslim family law legislations. This research, therefore, proposes reforms to key federal legislation on the protection of children and non- Muslim family law, specifically the Child Act 2001, the Law Reform (Marriage and Divorce) Act 1976, and the Guardianship of Infants Act 1961, and suggests including provisions that require consideration of the best interest of the child as the primary consideration, supported by legitimate guidelines.